Request a call back

Join NOW to get access to exclusive study material for best results

CBSE Class 9 Answered

Find the value of (x-a)³+(x-b)³+(x-c)³-3(x-a)(x-b)(x-c) when a+b+c=3×
Asked by akati.eti04 | 05 Mar, 2020, 06:51: PM
answered-by-expert Expert Answer
We know that, m3 + n3 + l3 - 3mnl = 0, if m + n + l = 0.  ... (i)
 
 
(x-a)³+(x-b)³+(x-c)³-3(x-a)(x-b)(x-c)
 
Here, 

m = x - a, n = x - b and l = x - c 

m+n+l = x - a + x - b + x - c = 3x - (a + b + c) = 3x - 3x = 0....(a + b + c = 0)
 
→ (x-a)³+(x-b)³+(x-c)³-3(x-a)(x-b)(x-c) = 0  .. from (i)
Answered by Yasmeen Khan | 06 Mar, 2020, 11:08: AM

Be a Top Scorer in the Exam with Test Series and Test Generator!

Enrol Now
×